A framework to analyse efficiency and governance of zakat institutions - Wahab, Norazlina Abd.; Abdul Rahman, Abdul Rahim (Emerald Group Publishing Limited, 2011)
This paper aims to present a conceptual model on the efficiency and governance of zakat institutions that are responsible in collecting, managing and distributing zakat in Malaysia. Zakat is an Islamic religious “tax” charged on the rich and well-to-do members of the community for distribution to the poor and the needy as well as other beneficiaries based on certain established criteria according to the Qur’an.The main aim of zakat is to protect the socio-economic welfare of the poor and the needy.